Organic Dust Toxic Syndrome (ODTS) - Deva Bachtiar; Agus Dwi Susanto (Faculty of Medicine Universitas Airlangga, 2016)
Organic dust toxic syndrome (ODTS) was manifestation of some acute symptoms, (same with acute hypersensitivity pneumonitis or extrinsic allergic alveolitis) with initially by flu like syndrome that were fever, malaise, myalgia, dry cough, dyspnea, and headache after exposure of organic dust in several hours. Etiology of ODTS usually from agricultural environment like hay, grain, straw, moldy, pollen, mycotoxins, bacteria and endotoxin. Organic dust toxic syndrome (ODTS) spontaneous recovery without sequele if patients avoid organic dust exposure immediately and avoid recurrent exposure. The best treatment were supportive therapy and preventive therapy from that etiology.